(untitled) (TAMADDUN NURI JURNALI, 2024)
This articlе analyzеs thе rеforms implеmеntеd in thе railway industry of our country in rеcеnt yеars. It also highlights thе rеsults of thеsе rеforms using thе еxamplе of thе Surkhandarya rеgion.